Association between gestational diabetes mellitus and adverse obstetric outcomes among women with advanced maternal age: A retrospective cohort study. Issue 40 (7th October 2022) - Deng, Lijun; Ning, Beibei; Yang, Hailan
Abstract : To explore the association of gestational diabetes mellitus (GDM) with maternal and neonatal adverse outcomes among women with advanced maternal age. This retrospective cohort study included 1551, 140 eligible pregnant women from the National Vital Statistics System database in 2017 to 2019, and all participants were divided into two groups: GDM group (n = 154, 646) and non-GDM group (n = 1396, 494). Univariate and multivariate logistic regression analyses were used to assess the association of GDM and maternal and neonatal outcomes; additionally, we also adopted subgroup analysis to analyze the association in detail based on gestational weight gain (GWG) levels. The risk of each adverse outcome was presented by using odds ratio (OR) and 95% confidence interval (CI). After adjusted some covariables, GDM increased the risk of neonatal assisted ventilation (OR = 1.380, 95% CI: 1.345–1.417), neonatal intensive care unit (NICU, OR = 1.436, 95% CI: 1.410–1.463) admission, neonatal low Apgar score at the fifth minutes (OR = 1.034, 95% CI: 1.018–1.051), neonatal high birth weight (OR = 1.132, 95% CI: 1.111–1.153), neonatal premature birth (OR = 1.244, 95% CI: 1.223–1.266), mothers entered intensive care unit (ICU, OR = 1.247, 95% CI: 1.107–1.406), and mothers took cesarean section (OR = 1.193, 95% CI: 1.180–1.207) among women with advanced maternal age. The study findings indicated that GDM was the risk factor for obstetric outcomes among women with advanced maternal age, which will have important implications for the management of GDM in women with advanced maternal age.